Ice temperature time-series from the southern sector of Larsen C Ice Shelf, Antarctic Peninsula, November-December 2022 ... - Hubbard, Bryn; Miles, Katie; RiPIce Project Team (NERC EDS UK Polar Data Centre, 2024)
The datasets are temperature time series from fibre-optic strings installed into two boreholes on Larsen C Ice Shelf, Antarctic Peninsula. Boreholes were drilled in December 2022 to 160 m to investigate the internal properties of a suture zone (Site 1) and a meteoric ice band (Site 2) of an ice shelf, as part of the NERC-funded RiPIce (Rift Propagation for Ice sheet models) research project. NERC standard grant NE/T008016/1. ... : The datasets are temperature time series recorded by fibre-optic-based distributed temperature sensing installed into two boreholes on Larsen C Ice Shelf, Antarctica, in November and December 2022. ...